Ancient Grandeur of the Vertebrate Neuropeptide Y System Shown by the Coelacanth Latimeria chalumnae - Larhammar, Dan; Bergqvist, Christina A. (Frontiers in Neuroscience, 2013)
The neuropeptide Y (NPY) family receptors and peptides have previously been characterized in several tetrapods, teleost fishes and in a holocephalan cartilaginous fish. This has shown that the ancestral NPY system in the jawed vertebrates consisted of the peptides NPY and PYY and seven G-protein-coupled receptors named Y1-Y8 (Y3 does not exist). The different vertebrate lineages have subsequently lost or gained a few receptor genes. For instance, the human genome has lost three of the seven receptors while the zebrafish has lost two and gained two receptor genes. Here we describe the NPY system of a representative of an early diverging lineage among the sarcopterygians, the West Indian Ocean coelacanth Latimeria chalumnae. The coelacanth was found to have retained all seven receptors from the ancestral jawed vertebrate. The receptors display the typical characteristics found in other vertebrates. Interestingly, the coelacanth was found to have the local duplicate of the PYY gene, called pancreatic polypeptide, previously only identified in tetrapods. Thus, this duplication took place very early in the sarcopterygian lineage, before the origin of tetrapods. These findings confirm the ancient complexity of the NPY system and show that mammals have lost more NPY receptors than any other vertebrate lineage. The coelacanth has all three peptides found in tetrapods and has retained the ancestral jawed vertebrate receptor repertoire with neither gains or losses.